THE EFFECT OF UTILIZATION OF HEALTH SERVICES AGAINST THE REPEATED VISITS OF THE PATIENT'S INTEREST OUTPATIENT IN HOSPITALS SLG KEDIRI - Puspitasari, Syndia; Siti Farida Noor Laila; Ema Mayasari (Universitas STRADA Indonesia, 2019)
Patient satisfaction depends on the quality of service. Stewardship is all the efforts made to meet the desires of its customers employees with services that will be provided. A Ministry is said to be good by the patient, is determined by the fact of whether the services provided can satisfy the needs of the patient, the patient's perception by using of the services received. The purpose of this research is to influence the utilization of health services against the interest of the visit in the RSUD SLG Kediri. This research uses a type of quantitative research descriptive research analytical survey method using cross sectional design. This is the entire research population the average outpatient visits a month in RSUD SLG Kediri who totaled 294 visits. the number of samples in this research is 170 respondents. Sample retrieval techniques in the study using the method of Purposive Sampling. Bound variables in this study is of interest re outpatient visits in RSUD SLG Kediri. The free variable used is the utilization of health services. The data collected with a questionnaire san tested with simple linear regression test. The results showed from 170 respondents, the majority of respondents said has been utilizing health service in RSUD SLG Kediri with a total of 94 respondents (55.3%). While the views of interest re-outpatient visits most respondents have done repeated outpatient visits in RSUD SLG Kediri with a total of 116 respondent (68.2%). There is the influence of utilization of health services against the interest of the repeated outpatient visits in RSUD SLG Kediri (p value 0.000 < 0.05 then Ho denied). Expected delivery of inputs, criticisms and suggestions regarding various matters related to the utilization of health services can motivate patients to perform repeated visits regularly.